Resilient finance: Navigating COVID-19 in the Indonesian capital market through an Islamic economic perspective - Sukmaningrum, Puji Sucia; Bin Mohd Dali, Nuradli Ridzwan Shah; Madyan, Muhammad; Laila, Nisful; Widiastuti, Tika (Universitas Negeri Surabaya, 2024)
This study examines investor behavior, measured by trading volume activity (TVA) and average abnormal return (AAR), during the COVID-19 pandemic in Indonesia. It provides a comprehensive analysis of the pandemic's impact on four key subsectors: pharmaceuticals, telecommunications, transportation, and food and beverages. Using an event study methodology with daily stock prices and trading volume data, the results reveal varying investor reactions across subsectors. Notably, the pharmaceutical subsector showed significant differences in TVA averages and AAR changes two days before and seven days after the pandemic announcement. In contrast, the food and beverages subsector experienced no significant change in TVA, but notable AAR fluctuations over 11 days. The telecommunications subsector demonstrated significant negative AAR differences post-announcement, despite no TVA changes, while the transportation subsector experienced a negative AAR difference over 11 days with no TVA variations. This detailed sectoral analysis offers valuable insights for stakeholders seeking to understand the differential impact of COVID-19 on various industries.